Drying kinetics of soy protein isolate-corn starch film during preparation and its moisture adsorption characteristics during storage - Tingwei Zhu; Jinyu Yang; Wanting Qin; Yadong Tian; Yingying Wang; Xingfeng Guo (Grain & Oil Science and Technology, 2023)
To better understand the mass transfer process of moisture in the soy protein isolate-corn starch (SPI-CS) films during preparation and storage process, the drying kinetics model of SPI-CS films with different formation conditions during the drying process and the moisture adsorption characteristics of the SPI-CS films under different humidity conditions were investigated. Within the range of experimental conditions, the moisture migration rule in the SPI-CS films during the drying preparation was combined with the Page model which was expressed as MR = exp (−ktn). It was found that the adsorption equilibrium needed shorter time (about 3 h) when the SPI-CS films existed in the environment with lower humidity (RH < 54%). Additionally, the second-order adsorption kinetic equation was successful to describe the moisture adsorption characteristic of the SPI-CS films during storage under different humidity conditions.